Pathogenesis of Gout from the Perspective of the Theory of Latent Pathogen: “Phlegm-Blood Stasis Latent in Collaterals and Pain Due to Obstruction” - Bian, Jiarui; Wu, Qian; Zhu, Jiang; Leng, Wei (Journal of Contemporary Medical Practice, 2026)
The clinical course of gout is characterized by insidious onset, sudden severe pain, and recurrent episodes. This pattern aligns closely with the pathogenic characteristics of latent pathogen—“hidden without manifestation, waiting for an opportunity to act, and triggered by inducing factors.” Therefore, gout can be classified under the category of “latent pathogen causing arthralgia.” However, the latent pathogen in gout is not exogenous six pathogenic factors, but rather endogenous phlegm turbidity and blood stasis. Initially, dysfunction of the spleen and kidney leads to impaired ascending of the clear and descending of the turbid, resulting in internal accumulation of dampness-turbidity and subsequent formation of phlegm turbidity. Subsequently, phlegm turbidity flows into the meridians and collaterals, lurking in the joints and bones. Over time, phlegm turbidity gives rise to blood stasis, and the two become intertwined, forming a composite latent pathogen that persists throughout the disease course and progressively deepens. When phlegm and blood stasis remain quiescent, the obstruction of collaterals is mild, and the healthy qi can still restrain them; thus, although pathogenic factors are present, pain does not occur. Once triggered by inducing factors such as dietary indiscretion, overexertion, or exogenous pathogenic influences, the latent pathogen suddenly becomes hyperactive, severely obstructing the collaterals and causing abrupt blockade of qi and blood, leading to the sudden onset of excruciating pain. The principle “pain due to obstruction” precisely captures the critical juncture at which the latent pathogen transforms from a hidden state to an active one, and from silence to outburst.